Bladder and Gastric Metastases from Lung Adenocarcinoma Harboring Codon 13 KRAS Mutation: a Case Report with Unusual Clinical Outcome. Issue 5 (September 2015) - Galetta, Domenico; Catino, Annamaria; Misino, Andrea; De Ceglie, Antonella; Logroscino, Antonio; Simone, Giovanni; Natalicchio, Maria Iole
Aims and background: Gastric and bladder metastases are rare in non-small-cell lung cancer (NSCLC) and the differential diagnosis with primary tumors requires an in-depth examination. KRAS gene mutations are the main oncogenic driver of lung adenocarcinoma in Caucasian patients, occurring in 25%-30% of cases, but their prognostic and predictive role is complex and not fully clarified. KRAS mutations in lung adenocarcinoma are considered negatively predictive for epidermal growth factor receptor tyrosine kinase inhibitors therapy as well as for adjuvant chemotherapy. In this report, the authors describe a case of lung adenocarcinoma harboring a codon 13 KRAS mutation detected in all the biopsies performed in unusual metastatic sites during an atypical disease course. Conclusions: Recently, a different prognostic significance of various KRAS mutations in lung adenocarcinoma has been suggested. Further studies on rare biomolecular alterations to identify subgroups of patients with different prognostic/predictive characteristics are needed.